A Cyclophilin OsCYP20–2 Interacts with OsSYF2 to Regulate Grain Length by Pre-mRNA Splicing - Qiang Ge; Yongyan Tang; Wei Luo; Jingyu Zhang; Kang Chong; Yunyuan Xu (Rice, 2020)
Abstract Background Grain size is one of the key agronomic traits that impact grain yield. Several regulatory pathways had been reported to participate in grain size determination via cell expansion or proliferation in rice. However, little is known about cyclophilin and spliceosome participation in grain shape regulation. Results Here, we identified OsCYP20–2, a cyclophilin that influences spliceosome assembly to determine grain length. oscyp20–2 t1, a knock out mutant of OsCYP20–2 caused by T-DNA insertion, produced shorter grains with deficient cell elongation. Through yeast two-hybrid screening and pull-down assays, OsSYF2, a pre-mRNA splicing factor, was identified as an interacting protein of OsCYP20–2. The phenotypes of transgenic lines indicated that OsSYF2 positively regulates grain length via its influence on cell expansion. Transcriptomic analysis showed that OsSYF2 controls the expression and pre-mRNA alternative splicing of genes involved in sugar metabolism. In addition, these two genes have similar effects on panicle architecture. Conclusions Taken together, OsSYF2, an interacting protein of OsCYP20–2, controls grain length and panicle architecture by regulating the alternative splicing of pre-mRNA involved in cell elongation and sugar metabolism.